The Analysis of Local Wisdom Learning Media Implementation at SD Negeri Gorua: Preserving Culture in a Frontier Area - Ledy Yanti Lessy; Pratiwi Febriana (Jurnal Ilmu Pendidikan (JIP) STKIP Kusuma Negara, 2026)
This research aims to analyze local wisdom-based learning media at SD Negeri Gorua and to identify challenges in its implementation. The study employed a descriptive qualitative approach. Research subjects included the school principal, teachers, students, parents, and local community figures. Data were collected through classroom observations, in-depth interviews, and documentation review. The collected data were analyzed through data reduction, data display, and conclusion drawing. The findings indicate that local wisdom-based learning media at SD Negeri Gorua have been implemented creatively and participatively by integrating various elements of local culture into cross-class and cross-subject learning activities. Teachers and the school principal demonstrated strong commitment to incorporating Galela culture into the learning process as a means of strengthening students’ character education and enhancing conceptual understanding. Local language use, traditional clothing, and the integration of traditional arts and sports into learning activities represent notable good practices. However, several challenges were identified, including limited learning resources, insufficient teacher training related to local wisdom integration, inadequate facilities, and weak collaboration among schools, the community, and government institutions. Despite these constraints, the implementation shows strong potential. The results of this study can serve as a reference for schools in frontier and remote areas in Indonesia contexts.